Quellen und Forschungen aus italienischen Archiven und Bibliotheken (De Gruyter, 2008)
Published by Deutsches Historisches Institut (DHI), Rome, since 1898, the historical specialist journal Quellen und Forschungen aus italienischen Archiven und Bibliotheken (QFIAB) presents articles and miscellanea (along with summaries in German and/or Italian) analyzing the relationship between Germany and Italy, as well as Italian history from the Early Middle Ages to the present.